Impact of Multivessel Coronary Disease With Chronic Total Occlusion on One-Year Mortality in Patients With Acute Myocardial Infarction - Lee, Ju Hwan; Park, Hun Sik; Ryu, Hyeon Min; Lee, Hyunsang; Bae, Myung Hwan; Lee, Jang Hoon; Yang, Dong Heon; Cho, Yongkeun; Chae, Shung Chull; Jun, Jae-Eun (Korean circulation journal, 2012)
The impact of multivessel coronary disease (MVD) with chronic total occlusion (CTO) on one-year mortality in patients with acute myocardial infarction (AMI) is not clearly known. We investigated the impact of MVD with concurrent CTO lesion on one-year mortality in patients with AMI. We studied 1008 consecutive patients who underwent coronary angiography between November 2005 and December 2008 with a diagnosis of AMI. Among 1008 patients, 432 patients (43%) had MVD, and 88 patients (8.7%) had CTO lesion. The one-year overall mortality was higher in patients with MVD than in patients with single vessel disease (SVD) (10.2% vs. 5.9%, p=0.012). However, the one-year overall mortality was not significantly higher in patients with CTO lesion than in patients without that lesion (12.5% vs. 7.3%, p=0.080). In multivariate analysis, independent predictors of one-year overall mortality were age older than 65 years {hazard ratio (HR) 2.41, 95% confidence interval (CI): 1.43 to 4.08}, Killip class ≥III (HR 3.59, 95% CI: 2.24 to 5.77), ST-elevation myocardial infarction (HR 2.45, 95% CI: 1.49 to 4.05) and MVD (HR 1.76, 95% CI: 1.07 to 2.89). Patients with MVD showed higher one-year mortality than patients with SVD. However, the presence of CTO was not an independent predictor of one-year mortality in this study that included patients with successfully revascularized CTO lesion.